Antispasmodic effects of Aloysia polystachya and A. gratissima tinctures and extracts are due to non-competitive inhibition of intestinal contractility induced by acethylcholine and calcium - Consolini, Alicia E. (2011)
The antispasmodic effects of acqueous extracts (AE) and tinctures (T) of Aloysia polystachya (Griseb.) Moldenke and Aloysia gratissima (Gillies & Hook.) Tronc., Verbenaceae, were studied on rat isolated ileum and duodenum. These plants are used for gastrointestinal disorders and as eupeptic in South America. Both AE non-competitively inhibited the dose-response curves (DRC) of ACh and the DRC of Ca2+ in high-[K+]o, as well as the T. The T of A. polystachya and A. gratissima respectively inhibited the ACh-DRC at the IC50 of 3.15±0.57 and 6.46±2.28 mg leaves/mL. The Ca2+-antagonist activity of both T occurred with IC50 respectively similar to those of the ACh-DRC, and was potentiated by the depolarization produced by 10 mM TEA, a blocker of K+-channels. The spasmolytic effect of T does not involve DA release and binding to D2, since it was not reduced by 10 μM metoclopramide. Also, T induced dose-dependent relaxation on the tonic contracture produced by high-[K+]o and ACh. By TLC there were detected in the leaves the presence of carvone, and flavonoids such as quercetin and hesperidin. By HPLC there were not found vitexin nor isovitexin, identified in A. citriodora. The monoterpene (-)-carvone non-competitively inhibited the ACh-DRC (pD ́2 of 4.0±0.1) and the DRC of Ca2+ (pD ́2 of 3.86±0.19), suggesting that the Ca2+-influx blockade is the mechanism of its antispasmodic effect. Results suggest that the antispasmodic effect of A. polystachya and A. gratissima are mostly explained by the non-competitive blockade of Ca+2 influx. It could be associated to the presence of flavonoids, and in the tinctures to some spasmolytic components of the essential oil such as carvone.